2018
DOI: 10.3389/fimmu.2018.01525
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Rheumatoid Inflammation by Sodium Butyrate Through Reciprocal Targeting of HDAC2 in Osteoclasts and HDAC8 in T Cells

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease caused by both genetic and environmental factors. Recently, investigators have focused on the gut microbiota, which is thought to be an environmental factor that affects the development of RA. Metabolites secreted by the gut microbiota maintain homeostasis in the gut through various mechanisms [e.g., butyrate, which is one of the major metabolites of gut microbiota, exerts an anti-inflammatory effect by activating G-protein-coupled receptors and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…The intraperitoneal administration of sodium butyrate at a high dose (100 mg/kg) suppresses the CIA by decreasing the T H 17/T REG ratio in DLNs [77] . In contrast, the T H 17/T REG ratio was not affected by the HAMSB diet in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The intraperitoneal administration of sodium butyrate at a high dose (100 mg/kg) suppresses the CIA by decreasing the T H 17/T REG ratio in DLNs [77] . In contrast, the T H 17/T REG ratio was not affected by the HAMSB diet in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts are multinucleated cells that are responsible for physiological and pathological bone resorption. SCFAs blunt osteoclast differentiation (97), and inhibition of HDAC activity is one mechanism whereby this occurs (98)(99)(100). For example, differentiation of primary bone marrow (BM) cells into osteoclasts is suppressed by butyrate and by trichostatin A, a known HDAC inhibitor (101).…”
Section: Effects Of Scfas On Osteoclasts and Bone Resorptionmentioning
confidence: 99%
“…Elements known to influence the mucosal barrier integrity include bacteria, their by-products and diet ( Horta-Baas et al, 2017 ; Guerreiro et al, 2018 ). Microbial by-products particularly short chain fatty acids (SCFA), including acetate, propionate, and butyrate have been linked to amelioration of arthritis development in CIA models ( Mizuno et al, 2017 ; Kim et al, 2018 ). Mizuno et al (2017) showed that oral administration of SCFA was able to decrease disease severity by decreasing Th1 cells, and increasing Treg cells thereby damping the immune response.…”
Section: The Gut Microbiome and Ramentioning
confidence: 99%